Aktivitas pegagan (Centella asiatica) pada dermatologi - Larysa Fernenda; Arba Pramundita Ramadhani; Yandi Syukri (Jurnal Sains Farmasi & Klinis, 2022)
Pegagan (Centella asiatica L.) is a herbal plant used in dermatology that has activity in treating skin diseases and skin lesions such as excoriations, burns, hypertrophic scars, antioxidants, anti-aging, skin whitening, and as a cosmetic ingredient. This review aims to collect data regarding the activity of Centella asiatica herb extracts in dermatology in both preclinical and clinical trial identification is done by searching literature through media Science Direct and Google Scholar using the keywords ''Centella asiatica'', ''Gotu kola'', ''dermatology'', ''cosmetics'', and ''whitening''. The search was based on the inclusion and exclusion criteria that had been set. The literature results show that the chemical constituents of Centella asiatica, such as asiaticoside, madecassoside, asiatic acid, and madecassic acid, are phytochemicals that play an essential role in the pharmacological activity of Centella asiatica in dermatology as a treatment and skin care. In both preclinical and clinical tests, it was shown that administration of Centella asiatica was capable of proliferating fibroblasts, activating the Smads pathway, increasing collagen synthesis, reducing metalloproteinase activity by increasing collagen deposition, and reducing melanin content in melanocytes so that it can modulate melanogenesis by inhibiting the expression of tyrosinase mRNA.